Budgeting and performance in the European Union A review by the OECD in the context of EU budget focused on results - Downes, Ronnie (OECD Publishing, 2017)
The European Union has a unique system of institutions and relationships between different levels of government resulting in a close attention to the performance aspects of budgeting. The EU system of budgeting for performance and results is advanced and highly specified, scoring higher than any OECD country in the standard index of performance budgeting frameworks. Aimed at improving the effectiveness of the EU budget in contributing to the achievement of EU objectives for growth, the EU Budget Focused on Results initiative is one that is gaining more focus and importance since it was launched in 2015. This report is the OECD's independent assessment of how the EU model of budgeting for performance and results compares with good practice around the world, in line with the long-established practice of OECD Budget Reviews; and offers suggestions for how the current reform agenda might be advanced. JEl Codes: H50, H61, H83 Keywords: Europe 2020, Multiannual Financial Framework, Annual Management and Performance Report, European Court of Audit, EU Budget Focused on Results
Keywords: Finance and Investment; Governance